Styrene-in-Water Emulsions Stabilized Solely by SiO2 Nanoparticles with Tunable Wettablity - Zhou, Haiou; Shi, Tiejun; Zhang, Fang; Zhou, Xun (Asian Journal of Chemistry, 2013)
Hydrophilic SiO2 nanoparticles were modified by ethacryloxypropyltrimethoxysilane (MPTMS). The surface wettablity was tuned by controlling the grafting extent of MPTMS and the surface element content was confirmed by XPS. Through measuring the contact angle, the surface wettablity was investigated. The results showed that when the mass ratio of MPTMS to SiO2 was 5 %, the contact angle was about 85º and the SiO2 nanoparticles could be partly wetted by both phases. The modified SiO2 nanoparticles were applied to stabilize styrene-in-water Pickering emulsion. The effect of surface wettability, particles concentrations on the stability and morphology of the Pickering emulsions was systematically studied. It was found that only SiO2 nanoparticles partly wetted by both phases were suitable to form Pickering emulsion and stable emulsion could not be obtained until the SiO2 nanoparticles concentrations were above 2 %.